The Effect of Temperature on Growth and Odour Production in Three Cyanobacteria Species - Reyhan Akçaalan; Zuhal Zengin (Aquatic Sciences and Engineering)
Taste and odour episodes associated with geosmin and 2-methylisoborneol (MIB) produced by Cyanobacteria are common problems affecting drinking water supplies. However, it is difficult to find the source and species responsible for taste and odour production. The aim of this study was to investigate the effect of temperature, one of the most important environmental factors, on the growth and odour production of Microcoleus sp. MCAS-MC01 and compare the results with those of two other odour-producing cyanobacteria (Oscillatoria sp. UHCC 0332 and Phormidium sp. NIVA-CYA 7) isolated and kept in culture collections from geographically different areas. Microcoleus sp. MCASMC01 is a newly isolated geosmin and MIB producer from Türkiye. After complaints arose from consumers in a nearby city, samples were taken and a cyanobacterium, Microcoleus sp., was isolated from the samples and grown in Z8 medium. Experiments were conducted at 20°C and 25°C for 10 weeks, and the growth and MIB-geosmin concentrations of cultures were monitored weekly. The geosmin concentration reached a maximum 65.73 µg/l and the maximum MIB concentration was 626.65 µg/l in the study. Higher temperature had a significant positive effect on MIB levels in Microcoleus sp. MCAS-MC01 and geosmin levels in Phormidium sp. NIVA-CYA7 (p<0.05). On the other hand, the temperature did not affect the growth of all three strains (p>0.05). The results showed that taste and odour problems are species-specific, and in some species, they are stimulated by an increase in temperature. This study contributes to the understanding of taste and odour problems in relation to temperature.